1920
DOI: 10.1039/ct9201701456
|View full text |Cite
|
Sign up to set email alerts
|

CLXII.—Researches on residual affinity and co-ordination. Part II. Acetylacetones of selenium and tellurium

Abstract: CLXI1.-Researcheson Residual A f l n i t y and CP ordination. Part I I . Acetylacetonev of Selenium and Tellurium.By GJLBERT T. MORGAN and HARRY DUGALD KEITH DREW. THE acetyla.cetolne derivahives of t,he metals, metlallaids, and nonmetals ma,y be classified into three main groups. I. Meta.llic ac:eltylacelttosnea, in which t'he principal valeaoiee of t$hel metal are complet,ely satisfied by the univalent, a.cetylamtone radidel, C5H702, such as t'he thallous, glucinum, oupric, zinc, sca,ndium, aluminium, chromi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
0

Year Published

1946
1946
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(28 citation statements)
references
References 0 publications
1
27
0
Order By: Relevance
“…The observation that these compounds formed a dioxime led Morgan' to propose a structure (1) where the bidentate ligand was bound to tellurium via the terminal carbon atoms, rather than through oxygen which is the normal mode for acetylacetone complexes. Recent X-ray crystallographic investigations3" have confirmed Morgan's conclusions and shown that the 6-membered ring adopts a chair conformation.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…The observation that these compounds formed a dioxime led Morgan' to propose a structure (1) where the bidentate ligand was bound to tellurium via the terminal carbon atoms, rather than through oxygen which is the normal mode for acetylacetone complexes. Recent X-ray crystallographic investigations3" have confirmed Morgan's conclusions and shown that the 6-membered ring adopts a chair conformation.…”
mentioning
confidence: 98%
“…classical series of papers published in the early 1920's Professor Sir Gilbert Morgan and co-workers-' reported that tellurium(1V) chloride combined with pentane-2,4-dione (acetylacetone) and other 1,3diketones to form dione tellurium dichlorides which, on bisulphite reduction, afforded stable crystalline tellurium(I1) compounds. The observation that these compounds formed a dioxime led Morgan' to propose a structure (1) where the bidentate ligand was bound to tellurium via the terminal carbon atoms, rather than through oxygen which is the normal mode for acetylacetone complexes. Recent X-ray crystallographic investigations3" have confirmed Morgan's conclusions and shown that the 6-membered ring adopts a chair conformation.…”
mentioning
confidence: 99%
“…Multidentate ligands have played a crucial role in the development of coordination chemistry, but it was only in 1920 that the word chelate was first introduced. In a paper on pentane-1,3-dionate complexes, Morgan and Drew [198] used the word chelate to describe a ligand which bound to a metal ion through two different atoms. The new word was introduced thus, "The adjective 'chelate,' derived from the great claw or 'chela' ('chely') of the lobster and other crustaceans, is suggested for these caliper-like groups which function as two associating units and fasten on to the central metallic atom so as to produce heterocyclic rings."…”
Section: Neologisms and New Terminologymentioning
confidence: 99%
“…The formation of complexes was discovered by the German scientist Alfred Werner in 1893 [1], and Gilbert Morgan and Harry Drew in 1920 [2] introduced chelation as a special type of complexation, assuming the process of the formation of complexes having cyclic structures with two or more bonds between binding sites. The important rule was formulated later by Lev Chugaev who found that chelates containing five to six member rings are usually the more stable when considering the different structures of complexes [3].…”
Section: Introductionmentioning
confidence: 99%